Platinum Complex Assemblies as Luminescent Probes and Tags for Drugs and Toxins in Water. Issue 8 (12th January 2017) - Sinn, Stephan; Biedermann, Frank; De Cola, Luisa
Abstract: A reactive phosphorescent probe for aza‐heterocyclic drugs and toxins was developed, affording a supramolecular emission‐switch‐on chemosensor in water. Complex formation of the heterocycles with a platinum(II) precursor proceeds readily at ambient conditions, allowing for facile analyte screening. Fifty‐two structurally diverse compounds were tested, out of which 23 pyridines, imidazoles, and triazoles formed strongly emissive complex aggregates. Importantly, they all can be clearly distinguished from each other through a principal component analysis, but often also by simple visual inspection, for example, by their emission color differences (large shifts from blue to red). Also, kinetic reaction profiles and time‐resolved emission features can provide valuable information for analyte distinction. The Pt II complexes can be applied as emissive labels for drugs and biomolecules, owing to their advantageous photophysical properties and chemical stability in biological media such as blood. Abstract : Analyte‐induced aggregation : An initially non‐luminescent reactive Pt II probe enables the discrimination of multiple analytes through different emission colors (see scheme).